Taxonomic reassessment of salamanders (genus Hynobius) from Tsushima Islands, Japan, with a resurrection of Hynobius tagoi Dunn, 1923 (Amphibia: Caudata) - Niwa, Keita; Nishikawa, Kanto; Matsui, Masafumi; Kanamori, Sally; Kuro-O, Masaki (Zootaxa, 2023)
To clarify the taxonomic status of salamanders from Tsushima Islands, Japan, we examined two species of salamanders, Hynobius tsuensis and Hynobius sp. from Tsushima Islands, and compared them with H. nebulosus from Kyushu. We found that the three taxa differ from each other in nuclear DNA, adult morphology, and egg-sac shape, and consider them to be independent species. Based on the investigation of type specimens of the synonyms, we identified Hynobius sp. as H. tagoi Dunn, 1923 and redescribe it herein. Also, we designate a neotype for H. tsuensis and redescribe H. tsuensis. The distribution areas of the two species partly overlap but they were distinguishable by their body colorations: H. tsuensis has uniformly blackish tail sides and a distinct yellow stripe on the upper tail edge; whereas H. tagoi has brown tail sides with numerous dark stippling and without a distinct yellow stripe on the upper tail edge.